DINAMIKA PEMENUHAN ASESOR PEMASYARAKATAN: STUDI PADA UNIT PELAKSANA TEKNIS PEMASYARAKATAN DI WILAYAH KALIMANTAN BARAT - Zulinda, Dea; Iskandar, Irvan Sebastian (Dinamika Governance: Jurnal Ilmu Administrasi Negara, 2024)
This research is motivated by the increasing inmate population and the crucial role of Correctional Assessors in ensuring effective rehabilitation and reintegration. With the enactment of Law No. 22 of 2022 on Corrections, the need for Correctional Assessors has become more urgent, particularly in Technical Implementation Units (UPT) that lack sufficient assessors. This study aims to analyze the fulfillment of the need for Correctional Assessors in West Kalimantan and identify the challenges in recruiting and training assessors. The research uses a qualitative method with descriptive analysis through interviews with staff from the Correctional Division, Heads of UPT, and operational staff. The analysis was conducted using the interactive model of Miles and Huberman, which includes data collection, reduction, presentation, and conclusion drawing. The findings reveal a gap between the available assessors and the demand, leading to increased workloads. The main obstacles include excessive workloads, limited training, geographical challenges, and a mismatch between responsibilities and compensation. This study recommends improving incentives, a more equitable distribution of assessors, and the development of continuous training programs to enhance the quality and quantity of correctional assessor.